Analysis of Supply Chain Management Effectiveness for Financial System of Institutes - Anik Yuesti; Ni Made Dwi Ratnadi; Gregorious Paulus Tahu (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this study is to analyze the effectiveness of the implementation of the supply chain management as the Internal Financial Control System in Financial system of the universites. This research method uses a type of critical qualitative research that is describing, describing, describing, assessing a condition, evaluating, and providing recommendations to SPI with observation, interviews, questionnaires, and document studies. The results reflected the improvement in the efficiency and the effectiveness of SC strategy in connection with the company’s short-term strategic financial objectives. The analysis showed that any improvement in the SC operations’ performance will lead to better supply chain management (SCM), and consequently enhance the company’s overall financial performance. An improvement in SC performance as well as financial performance has been shown for the three conditions (optimistic, normal and pessimistic) following the proposed procedure.In increasing the effectiveness of the implementation of the internal control system at the ISI Denpasar, it needs to be supported by several things including: the application of recruitment patterns and employee career development, the application of risk identification and analysis methodologies, improving communication with external parties, implementing follow-up audit procedures and attention to completeness documentation of the results of activities. The paper follows a systems view which can help in determining the most appropriate SC strategy with regard to targeted financial objectives in education ssytem. This paper benefits from data extracted from a institutes by evaluating the applicability of the model developed under a different set of scenarios.